2016
DOI: 10.1352/1934-9556-54.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Who Am I? A Life Story Intervention for Persons With Intellectual Disability and Psychiatric Problems

Abstract: This article describes an innovative intervention based on narrative and life review therapy that is tailored to people with intellectual disability (ID) and psychiatric problems. The current study provides a first evaluation of the intervention. A symptom checklist (SCL-90) was used in a pre- and post-follow-up design, and a qualitative evaluation of the intervention was carried out with 25 participants. Results showed large changes in psychiatric symptoms, in particular on depression, anxiety, obsessive-comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…This is in line with previous studies that underscore the importance of participation by the person and other relevant stakeholders (Gore et al, ). In addition to previous studies that reported on the views of people with ID on specific therapies for different challenging behaviours (Hassiotis et al, ; Hays, Murphy, Langdon, Rose, & Reed, ; Pert et al, ; Westerhof, Beernink, & Sools, ), the present authors were able to help reduce the identified lack of information on experiences of specific psychological interventions (Griffith et al, ) by collecting positive attitudes on EMDR, group therapy regarding addiction and assertiveness courses. However, most interviewees were most enthusiastic about doing sports or other physical activities, perhaps because these are more “visible” and fun.…”
Section: Discussionmentioning
confidence: 94%
“…This is in line with previous studies that underscore the importance of participation by the person and other relevant stakeholders (Gore et al, ). In addition to previous studies that reported on the views of people with ID on specific therapies for different challenging behaviours (Hassiotis et al, ; Hays, Murphy, Langdon, Rose, & Reed, ; Pert et al, ; Westerhof, Beernink, & Sools, ), the present authors were able to help reduce the identified lack of information on experiences of specific psychological interventions (Griffith et al, ) by collecting positive attitudes on EMDR, group therapy regarding addiction and assertiveness courses. However, most interviewees were most enthusiastic about doing sports or other physical activities, perhaps because these are more “visible” and fun.…”
Section: Discussionmentioning
confidence: 94%
“…Participants in the experimental condition followed the intervention My Lifestory. The present authors previously used the name Who am I?, but the content of the intervention is the same as described in detail in Westerhof et al (2016). My Lifestory consists of 17 weekly structured one-to-one or group sessions, each lasting for 1.5-2 hr.…”
Section: Conditionsmentioning
confidence: 99%
“…Previous research asking people with learning disabilities about their experiences of undergoing psychological therapy has found that people valued specific techniques used as part of the particular intervention they were receiving, but placed more emphasis on the non-specific aspects of their therapy such as the therapeutic relationship, being listened to and respected by the therapist, and being able to talk about their lives. 74,75 People with learning disabilities participating in a group intervention found it challenging to talk about their individual feelings in a group context. 75 Having a supporter (whether a family member or a paid carer) with the person with learning disabilities during at least part of a psychological intervention has been suggested as an important adjustment to the routine therapy process, to assist people undergoing the therapy with motivation and activities between therapy sessions.…”
Section: Chapter 7 Qualitative Study Introductionmentioning
confidence: 99%
“…74,75 People with learning disabilities participating in a group intervention found it challenging to talk about their individual feelings in a group context. 75 Having a supporter (whether a family member or a paid carer) with the person with learning disabilities during at least part of a psychological intervention has been suggested as an important adjustment to the routine therapy process, to assist people undergoing the therapy with motivation and activities between therapy sessions. [76][77][78] Research on the impact of the presence of a member of staff as a supporter during psychological interventions with people with learning disabilities is mixed; 74,79 however, research asking supporters directly about their experiences is lacking.…”
Section: Chapter 7 Qualitative Study Introductionmentioning
confidence: 99%